Biocompatibility of a Magnetic Tunnel Junction Sensor Array for the Detection of Neuronal Signals in Culture - Moretti, Daniela; DiFrancesco, Mattia Lorenzo; Sharma, Parikshit Pratim; Dante, Silvia; Albisetti, Edoardo; Monticelli, Marco; Bertacco, Riccardo; Petti, Daniela; Baldelli, Pietro; Benfenati, Fabio (Frontiers in Neuroscience, 2018)
Magnetoencephalography has been established nowadays as a crucial in vivo technique for clinical and diagnostic applications due to its unprecedented spatial and temporal resolution and its non-invasiveness methods. However, the innate nature of the biomagnetic signals derived from active biological tissue is still largely unknown. One alternative possibility for in vitro analysis is the use of magnetic sensor arrays based on Giant Magnetoresistance. However, these sensors have never been used to perform long-term in vitro studies mainly due to critical biocompatibility issues with neurons in culture. In this study, we present the first biomagnetic chip based on magnetic tunnel junction (MTJ) technology for cell culture studies and show the biocompatibility of these sensors. We could obtain a full biocompatibility of the system through the planarization of the sensors and the use of a capping three-layer of SiO2/Si3N4/SiO2. We grew primary neurons up to 20 days on the top of our devices and obtained proper functionality and viability of the overlying neuronal networks. At the same time, MTJ sensors kept their performances unchanged for several weeks in contact with neurons and neuronal medium. These results pave the way to the development of high performing biomagnetic sensing technology for the electrophysiology of in vitro systems, in analogy with Multi Electrode Arrays.